Democracy at Risk : How Political Choices Undermine Citizen Participation, and What We Can Do About It - Macedo, Stephen, 1957- (Book collections on Project MUSE., 2005)
"Documents how recent trends in civic engagement have been shaped by political institutions and public policies and recommends ways to increase the amount, quality, and distribution of civic engagement, focusing on elections, the metropolis, and the nonprofit sector and philanthropy"--Provided by publisher